2020
DOI: 10.48550/arxiv.2012.08666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weinstein handlebodies for complements of smoothed toric divisors

Abstract: We study the interactions between toric manifolds and Weinstein handlebodies. We define a partially-centered condition on a Delzant polytope, which we prove ensures that the complement of a corresponding partial smoothing of the toric divisor supports an explicit Weinstein structure. Many examples which fail this condition also fail to have Weinstein (or even exact) complement to the partially smoothed divisor. We investigate the combinatorial possibilities of Delzant polytopes that realize such Weinstein doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Specifically the root of the tree is (1, 1, 1) which has a single child vertex (1, 1, 2). The vertex (1, 1, 2) also has a single child vertex (1,2,5). Any other vertex (𝑝 1 , 𝑝 2 , 𝑝 3 ) has two child vertices; the left child is (𝑝 2 , 𝑝 3 , 3𝑝 2 𝑝 3 − 𝑝 1 ), and the right child is (𝑝…”
Section: Markov Triples and The Markov Treementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically the root of the tree is (1, 1, 1) which has a single child vertex (1, 1, 2). The vertex (1, 1, 2) also has a single child vertex (1,2,5). Any other vertex (𝑝 1 , 𝑝 2 , 𝑝 3 ) has two child vertices; the left child is (𝑝 2 , 𝑝 3 , 3𝑝 2 𝑝 3 − 𝑝 1 ), and the right child is (𝑝…”
Section: Markov Triples and The Markov Treementioning
confidence: 99%
“…We will give explicit handle descriptions corresponding to these almost toric pictures of ℂP 2 and transferring the cut (giving yet another proof that 𝑋 𝑝 1 ,𝑝 2 ,𝑝 3 is diffeomorphic to ℂ𝑃 2 ) in Section 5.3. In the literature the relationship between almost toric pictures and symplectic handlebodies has been studied for Weinstein domains [1], but not for closed symplectic manifolds. This handlebody description of transferring the cut is what lies behind our proof of Theorem 1.1 in Section 5.1.…”
Section: Mutation and The Almost Toric Geometry Of ℂPmentioning
confidence: 99%
“…For an example of an application of Theorem 1.6 and Corollary 5.1, see [2] where the authors showed that the Weinstein complement of certain divisors in toric 4-manifolds are not flexible.…”
mentioning
confidence: 99%